Analisis Risiko Kebisingan di Sekolah Dasar Negeri 47/VI Kota Jambi Akibat Arus Lalu Lintas - Suci Anggela Febrianti; Febri Juita Anggraini; Zuli Rodhiyah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
The high volume of transportation activity in Jambi City, particularly in front of SD Negeri 47/VI, generates noise that contributes to noise pollution. This research aims to determine the noise level and determine the risks posed by noise due to traffic flow. The noise value is measured by a Sound Level Meter and the number of vehicles is measured by a Hand Tally Counter. This research uses a questionnaire given to students and will be analyzed using the Odds Ratio (OR) risk analysis method. The results of noise level measurements exceed the Quality Standards of PERMEN LH NO.48 of 1996, with the highest measurement results occurring on tuesday at L1 measurements (06.30-08.00 am) at sampling point D (classrooms that are close to the noise source) with the noise level being 65.92 dBA. The results of the analysis of noise risks that can be caused are, feeling disturbed by noise with an OR value of 10.9, difficulty hearing with an OR value of 1.6, communication disorders with an OR value of 3.5, difficulty concentrating with an OR value of 3.9 and psychological disorders with OR 0.4.